2014
DOI: 10.1186/1472-6807-14-14
|View full text |Cite
|
Sign up to set email alerts
|

High resolution structure of cleaved Serpin 42 Da from Drosophila melanogaster

Abstract: BackgroundThe Drosophila melanogaster Serpin 42 Da gene (previously Serpin 4) encodes a serine protease inhibitor that is capable of remarkable functional diversity through the alternative splicing of four different reactive centre loop exons. Eight protein isoforms of Serpin 42 Da have been identified to date, targeting the protease inhibitor to both different proteases and cellular locations. Biochemical and genetic studies suggest that Serpin 42 Da inhibits target proteases through the classical serpin ‘sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Currently, the structures of seven different arthropod serpins have been solved from M. sexta [122,123], D. melanogaster [124], An. gambiae [125], B. mori [126], I. ricinus [108], and T. molitor [35].…”
Section: Structure/function Aspects Of Arthropod Serpinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, the structures of seven different arthropod serpins have been solved from M. sexta [122,123], D. melanogaster [124], An. gambiae [125], B. mori [126], I. ricinus [108], and T. molitor [35].…”
Section: Structure/function Aspects Of Arthropod Serpinsmentioning
confidence: 99%
“…Two arthropod serpin structures have been determined in their cleaved, inactivated form: D. melanogaster Spn4 (Serpin 42 Da) (pdb codes: 4P0O and 4P0F, [124]) and I. ricinus IRS-2 (pdb code 3NDA, [148]) (Fig. 4E), previously discussed in Sections 2.3 and 4.2, respectively.…”
Section: Structure/function Aspects Of Arthropod Serpinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Like many serpins, the C-terminus of OcSPI contains a potential RCL region, including the hinge region and proteinase cleavage site characteristic of active proteinase inhibitors (Osterwalder et al, 2004;Garrett et al, 2009). Additionally, OcSPI contains Phe and Phe residues at the putative P1-P1′ positions, but did not contain a tetrapeptide reminiscent of an ER retention signal, as observed in Drosophila serpin4.1 and vertebrate neuroserpins (Osterwalder et al, 2004;Garrett et al, 2009;Ellisdon et al, 2014). The C-terminal portions of the OcSPI protein (including the conserved hinge region, the reactive site, and the serpin signature region) exhibited 42% protein sequence identity to the Drosophila Serpin27A (Osterwalder et al, 2004).…”
Section: Discussionmentioning
confidence: 83%
“…In Drosophila, serpin 4 is the closest vertebrate neuroserpin homolog and functions as a neuroserpin-like inhibitor of subtilisin-like proprotein convertases (Osterwalder et al, 2004). A recent study demonstrated that the D. melanogaster Spn42Da (previously known as serpin 4) encodes eight protein isoforms (Ellisdon et al, 2014) that inhibit furin-, subtilase-and chymotrypsin-like serine proteases and papain-like cysteine proteases (Oley et al, 2004;Osterwalder et al, 2004;Richer et al, 2004). From these results, Spn42Da isoforms potentially improve immune defense by inhibiting pathogenic proteolytic enzymes (Brüning et al, 2007).…”
Section: Introductionmentioning
confidence: 93%